2014
DOI: 10.1007/s00425-014-2079-1
|View full text |Cite
|
Sign up to set email alerts
|

Not all anthocyanins are born equal: distinct patterns induced by stress in Arabidopsis

Abstract: Main ConclusionDifferent abiotic stress conditions induce distinct sets of anthocyanins, indicating that anthocyanins have different biological functions, or that decoration patterns of each anthocyanin are used for unique purposes during stress.The induction of anthocyanin accumulation in vegetative tissues is often considered to be a response of plants to biotic or abiotic stress conditions. Arabidopsis thaliana (Arabidopsis) accumulates over 20 anthocyanins derived from the anthocyanidin cyanidin in an orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 146 publications
(113 citation statements)
references
References 54 publications
8
105
0
Order By: Relevance
“…Anthocyanins are commonly induced in plant vegetative tissues in response to a number of different abiotic stresses including drought, salinity, excess light, sub-or supra-optimal temperatures, and nitrogen and phosphorous deficiency. [2][3][4][5][6][7][8] The proposed roles of anthocyanins during abiotic stresses include quenching of ROS, 9,10 photoprotection, 11,12 stress signaling, 13,14 and xenohormesis (i.e., the biological principle that relates bioactive compounds in environmentally stressed plants and the increase in stress resistance and survival in animals that feed from them). 15,16 Plants as a group produce hundreds of structurally distinct anthocyanin species.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Anthocyanins are commonly induced in plant vegetative tissues in response to a number of different abiotic stresses including drought, salinity, excess light, sub-or supra-optimal temperatures, and nitrogen and phosphorous deficiency. [2][3][4][5][6][7][8] The proposed roles of anthocyanins during abiotic stresses include quenching of ROS, 9,10 photoprotection, 11,12 stress signaling, 13,14 and xenohormesis (i.e., the biological principle that relates bioactive compounds in environmentally stressed plants and the increase in stress resistance and survival in animals that feed from them). 15,16 Plants as a group produce hundreds of structurally distinct anthocyanin species.…”
mentioning
confidence: 99%
“…4 We analyzed seedlings grown in 8 abiotic stress conditions, including high salinity, cold, and an artificial stress medium termed anthocyanin induction condition (AIC), which consists of 3% sucrose and no additional nutrients. The fact that distinct profiles of anthocyanins are induced by different abiotic stresses suggested that different anthocyanins, or profiles of anthocyanins, have different functions in planta.…”
mentioning
confidence: 99%
See 3 more Smart Citations